Self-regulated vocabulary learning in Indonesian higher education: Strategies, digital tools, and the awareness-action gap - Jovita, Clarence; Daud, Afrianto; Tri Purwanti, Indah (Teaching English as a Foreign Language Journal, 2025)
Vocabulary acquisition is a cornerstone of language proficiency, yet many university students face difficulties in managing their learning autonomously. Self-regulated learning (SRL) strategies offer potential for greater independence, but their actual implementation in English as a Foreign Language (EFL) contexts remains underexplored. This study examines the lived experiences of EFL students in applying SRL strategies for vocabulary learning, focusing on how they adapt these strategies to their individual goals, contexts, and challenges. A qualitative phenomenological design was employed, involving semi-structured interviews with 14 second-semester English Study Program students at Universitas Riau. Data were analyzed through thematic analysis, guided by Zimmerman’s SRL model. Three themes emerged. First, students flexibly applied SRL strategies by adapting Zimmerman’s framework to personal goals, moods, and contexts, though systematic goal-setting was often absent. Second, digital tools such as Duolingo, TikTok, and YouTube shaped personalized learning ecosystems that blended formal study with informal media, underscoring both creativity and the need for digital self-regulation. Third, students reported difficulties in sustaining consistent SRL due to challenges in time management, emotional regulation, and transforming receptive into productive vocabulary. The study highlights how EFL learners adapt SRL in dynamic and non-linear ways, extending Zimmerman’s model to digital and affective dimensions of vocabulary learning. Pedagogically, findings underscore the need for structured support to help students bridge the gap between strategic awareness and consistent application, while offering directions for future research on fostering resilient autonomous learning habits.